2015
DOI: 10.7324/japs.2015.50907
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and tyrosinase inhibition activities of and #945;- mangostin and Garcinia mangostana Linn. pericarp extracts

Abstract: The methanol, ethyl acetate and petroleum ether crude extracts of mangosteen pericarp and αmangostin were evaluated for the antioxidant capacity and tyrosinase inhibition properties. The ferric reducing antioxidant power (FRAP) assay was used to investigate their antioxidant capacity. Tyrosinase inhibition effect was evaluated using mushroom tyrosinase inhibition assay. Methanol extract has higher antioxidant reducing capacity (m= 1.621), compared to the rest of the extracts. Meanwhile, ethyl acetate extract a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Previously, α-mangostin was also proved that can down-regulate the mushroom tyrosinase activity by in vitro. assay [ 21 ]. Many similar studies about natural extracts or compounds have shown that they directly inhibit the catalytic activity of tyrosinase by regulating the molecular structure, but cell lysate included not only tyrosinase but also TRP-1 and TRP-2.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, α-mangostin was also proved that can down-regulate the mushroom tyrosinase activity by in vitro. assay [ 21 ]. Many similar studies about natural extracts or compounds have shown that they directly inhibit the catalytic activity of tyrosinase by regulating the molecular structure, but cell lysate included not only tyrosinase but also TRP-1 and TRP-2.…”
Section: Discussionmentioning
confidence: 99%
“…0.5% (w/w) mangosteen nanoparticle loaded gel and 1% clindamycin gel did not significantly improve PIH. Even if the mangosteen fruit rind extract exhibited potent anti‐inflammatory and antioxidant properties, alpha‐mangostin was previously reported to promote tyrosinase inhibition effect . PIH occurred from the overproduction of melanin by melanocytes following the late stage of inflammation and other factors, such as sun exposure which might require longer duration of MNLG treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also revealed that -keto group in mangosteen peel have a structure such as dihydroxyphenylalanine (DOPA) or tyrosine that could prevent melanogenesis in skin-induced UVB radiation [15], [16]. Physical and chemical characterization of mangosteen peel has been already reported by previous studies [11], [12], [13], [14], [15], [16]; however, the potency of the mangosteen peel extract-based cream and its mechanism in skin hyperpigmentation is still unknown.…”
Section: Introductionmentioning
confidence: 95%
“…possesses antioxidant, anticancer, anti-inflammatory, and antibacterial activity [11]. α-mMangostin, the primary constituent of xanthones in mangosteen peel has potency as an anti-tyrosinase for treating issues of skin hyperpigmentation [12]. The previous studies reported that the mangosteen peel contains phenolic and flavonoid polyphenols, both of which include phenol rings with one or more hydroxyl substituents that may scavenge ROS as a result of exposure to UVB radiation [13], [14].…”
Section: Introductionmentioning
confidence: 99%